2016
DOI: 10.1186/s12883-016-0609-0
|View full text |Cite|
|
Sign up to set email alerts
|

PRISM II: an open-label study to assess effectiveness of dextromethorphan/quinidine for pseudobulbar affect in patients with dementia, stroke or traumatic brain injury

Abstract: BackgroundPhase 3 trials supporting dextromethorphan/quinidine (DM/Q) use as a treatment for pseudobulbar affect (PBA) were conducted in patients with amyotrophic lateral sclerosis (ALS) or multiple sclerosis (MS). The PRISM II study provides additional DM/Q experience with PBA secondary to dementia, stroke, or traumatic brain injury (TBI).MethodsParticipants in this open-label, multicenter, 90-day trial received DM/Q 20/10 mg twice daily. The primary outcome was the Center for Neurologic Study-Lability Scale … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 35 publications
(40 reference statements)
1
18
0
1
Order By: Relevance
“…Patients treated with DM/Q 20/10 mg experienced improvements across multiple assessments, including significant reductions in CNS‐LS scores and PBA episodes, improvements in CGI‐C and PGI‐C, SIS, QOL‐VAS, MMSE, and PHQ‐9. These results were consistent with those for other PRISM II patient cohorts with PBA following dementia or TBI . Further, an a priori analysis comparing results from this open‐label trial with results from placebo‐controlled phase 3 studies enrolling patients with PBA caused by ALS or MS showed a consistent effect based on confidence intervals for change from baseline mean CNS‐LS .…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Patients treated with DM/Q 20/10 mg experienced improvements across multiple assessments, including significant reductions in CNS‐LS scores and PBA episodes, improvements in CGI‐C and PGI‐C, SIS, QOL‐VAS, MMSE, and PHQ‐9. These results were consistent with those for other PRISM II patient cohorts with PBA following dementia or TBI . Further, an a priori analysis comparing results from this open‐label trial with results from placebo‐controlled phase 3 studies enrolling patients with PBA caused by ALS or MS showed a consistent effect based on confidence intervals for change from baseline mean CNS‐LS .…”
Section: Discussionsupporting
confidence: 85%
“…The Pseudobulbar Affect Registry Investigating Symptom Management II (PRISM II) was designed to evaluate DM/Q effectiveness and safety for PBA treatment in patients with stroke, traumatic brain injury (TBI), or dementia—3 neurologic conditions that commonly cause PBA. Results from the overall study population (N = 367) as well as the cohort of PBA patients with dementia (n = 134) have been reported previously . Safety, tolerability, and efficacy results for the patients with PBA following stroke are reported here.…”
Section: Introductionmentioning
confidence: 80%
“…The fatality and disability rates of TBI are the highest among traumas of human organs (1). The incidence of TBI in USA is ~2%, and 500,000 new TBI cases are recorded annually, including 10% severe TBI, which leads to ~20,000 mortality and 30,000 disability cases, resulting in significant direct and indirect economic losses (2). With the rapid development of the global economy and modern transportation, TBI has become an important human health issue (1).…”
Section: Introductionmentioning
confidence: 99%
“…Although PBA is considered an affective disorder independent of mood, both antidepressants (such as serotonin reuptake inhibitors and tricyclic antidepressants) and dextromethorphan/quinidine (DM/Q) are known to be effective in the treatment of PBA symptoms. [18][19][20] The mood effects of DM/Q are not established, and our findings suggest the possibility that patients with parkinsonism could preferentially benefit from treatment with antidepressants for dual management of both PBA and mood symptoms with a single agent.…”
Section: Discussionmentioning
confidence: 95%